1999
DOI: 10.1007/bf02976443
|View full text |Cite
|
Sign up to set email alerts
|

Advanced method for determination of omeprazole in plasma by HPLC

Abstract: An advanced and sensitive high-performance liquid chromatographic (HPLC) method for determination of omeprazole in human plasma has been developed. After omeprazole was extracted from plasma with diethylether, the organic phase was transferred to another tube and trapped back with 0.1 N NaOH solution. The alkaline aqueous layer was injected into a reversed-phase C8 column. Lansoprazole was used as an internal standard. The mobile phase consisted of 30% of acetonitrile and 70% of 0.2 M KH2P04, pH 7.0. Recoverie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 5 publications
0
29
0
Order By: Relevance
“…To obtain chromatograms with good separation various columns, mixtures of mobile phase and different flow rates were investigated. For the assay of PPIs in human plasma a ODS-A C 18 was found to be better than Nova-Pak C 18 or inertsil ODS-3V C 18 . Various mixtures of phosphate buffer/acetonitrile were used as mobile phase and results indicated that phosphate buffer (10 mM)/acetonitrile (53/47, adjusted pH to 7.3 with triethylamine) gives the best resolution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain chromatograms with good separation various columns, mixtures of mobile phase and different flow rates were investigated. For the assay of PPIs in human plasma a ODS-A C 18 was found to be better than Nova-Pak C 18 or inertsil ODS-3V C 18 . Various mixtures of phosphate buffer/acetonitrile were used as mobile phase and results indicated that phosphate buffer (10 mM)/acetonitrile (53/47, adjusted pH to 7.3 with triethylamine) gives the best resolution.…”
Section: Resultsmentioning
confidence: 99%
“…Chromatographic separation of PPIs was achieved using a TRACER EXCEL 120 ODS-A (5 µm 250 mm×4.6 mm i.d, Teknokroma) reverse phase analytical column with a µBondapak™ C 18 Guard column (5 μm, 120 Aº, Ireland). The mobile phase consisting of a mixture of phosphate buffer (10 mM)/acetonitrile (53/47, v/v adjusted pH to 7.3 with triethylamine).…”
Section: Apparatus and Chromatographic Conditionsmentioning
confidence: 99%
“…For clinical pharmacology studies, a simple and rapid extraction step is necessary, which is why liquid-liquid extraction was chosen. This extraction method was also used by Kang et al, 1999;Wang et al, 2004;Desmet et al, 2010; but with higher limit of quantification by Bharathi et al, 2009A solid phase extraction of 90% efficiency was proposed by Woolf et al, 1998;Kanazawa et al, 2004 but it is more expensive than liquid-liquid extraction. The simple protein precipitation extraction procedure was investigated but proved to be unacceptable due to interference and low sensitivity.…”
Section: Application Of the Methods In Human Subjectsmentioning
confidence: 99%
“…Assay of omeprazole and omeprazole sulfone has been reported using semi-micro column liquid chromatography with mixed-function precolumn (Yim et al, 2001). Several HPLC methods have been published for quantitatively determining omeprazole levels in human plasma (Vittal et al, 2009;DeSmet et al, 2010;TsingHua 2004;Bharathi et al, 2009;Kanazawa et al, 2004;Wang et al, 2004 andKang et al, 1999). The methods are isocratic and gradient HPLC (or) HPLC with column switching liquid chromatography mass spectrometry (LC-MS/MS).…”
Section: Introductionmentioning
confidence: 99%
“…The reaction was terminated by addition of 1 ml of diethyl ether after 5 min incubation. Omeprazole was measured by a reported HPLC method [14]. The kinetic constants (K m and V max ) for the disappearance of omeprazole were calculated using a non-linear regression method [15].…”
Section: Preparation Of Hepatic and Intestinal Microsomesmentioning
confidence: 99%